Controlled Substrate Destruction Using Nanothermite. Issue 6 (1st June 2017) - Fleck, Trevor J.; Ramachandran, Raghav; Murray, Allison K.; Novotny, Whitney A.; Chiu, George T.‐C.; Gunduz, I. Emre; Son, Steven F.; Rhoads, Jeffrey F.
Abstract: The experiments described in this paper look to further transient electronic device development by exploring the fracturing capabilities of aluminum copper (II) oxide and aluminum bismuth (III) oxide nanothermites. In particular, a quick, inexpensive test was developed that was able to characterize the substrate fracturing capability of these selectively deposited energetic materials. Using this test, aluminum bismuth (III) oxide nanothermite with near stoichiometric composition was shown to be an effective material for fracturing silicon wafers of two different thicknesses for the configuration considered. Nanothermites were deposited at various equivalence ratios, resulting in a range of damage, which enables material preparation in a given practical application to be based on the desired level of resultant fracturing. This data was subsequently compared with thrust measurements and gas shock formation in an effort to correlate thrust production to the severity of fracturing produced. Abstract :